Enhancing historical consciousness in history education through integrating STEM approach and historical thinking skill - Pratama, Rinaldo Adi; Saputra, Muhammad Adi; Hikmawaty, Lisna (Intelektual Pustaka Media Utama, 2024)
The research explores the potential of incorporating science, technology, engineering, and mathematics (STEM) education approach and critical thinking to enhance historical consciousness. The study employs an ex post facto quantitative method, specifically a correlational design to analyse the variables. The research population comprises 425 students from diverse backgrounds in Banten Province schools that have implemented the STEM approach. A sample size of 202 students is determined using a predefined error rate. Data collection involves tests and questionnaires assessing historical thinking skills, STEM approaches, and historical consciousness. Statistical analysis, including partial and simultaneous multiple correlation tests, reveals a significant and very strong positive relationship between STEM approach, historical thinking skills, and historical consciousness. This suggests that the interplay of these factors enhances history learning and encourages a deeper understanding of historical events, promoting critical thinking, and historical consciousness. The study emphasizes the importance of integrating STEM methodologies into history education to provide students with a holistic understanding of historical events and their societal implications. Such an approach bridges the gap between STEM and history, fostering interdisciplinary collaboration and promoting informed and empathetic citizens. Future research should explore diverse samples, employ qualitative methods, and investigate curriculum designs and teaching strategies that effectively integrate STEM and history education.